Chemical and Biological Investigations of Leaves of Abroma augusta Linn. - Rahman, SM Ashikur; Rahman, Muhammed Mahfuzur; Hossain, Md Aslam; Rashid, Mohammad A (Bangladesh Pharmaceutical Journal, 2016)
Abstract not available Bangladesh Pharmaceutical Journal 19(2): 233-236, 2016